Water fall : a teardrop novel - Kate, Lauren (Kate, Lauren. Teardrop series, 2015)
Eureka, a girl whose tears have the power to raise the lost continent of Atlantis and who travels across the ocean with Cat, her family, and Ander, the gorgeous and mysterious Seedbearer who promises to help her, has the chance to save the world might have to give up everything--even love.